PATHOGENIC MICROORGANISM AS AN ELEMENT OF FORENSIC CHARACTERISTICS OF BIOTERRORISM (Journal of actual problems of jurisprudence, 2019)
This article is devoted to forensic research of the damage circumstances by pathogenic microorganism in the environment after a terrorist attack. The topic is relevant in that it has not yet been studied in forensic such notions as «especially dangerous infections», «biological agents», «bacteriological weapons», «biological weapons», «pathogenicity», «contagious properties», etc. were not considered in the literature. In forensic science, the properties of biological agents of biological weapons developed to date, the mechanism and nature of trace formation in the material situation where a terrorist act can be committed using these means are not systematized. The issues of technical and forensic support for conducting investigative actions were not considered, for example, when inspecting the scene of an incident, if an act of terrorism was committed, there are no recommendations on the tactical features of investigating this category of crimes, and the specialists are not known in what procedural form. Specialists should be established to prove the guilt of the terrorist (s), and other issues are not developed as well. of terrorism.The purpose of research, based on the properties of pathogenic microorganisms of natural origin and biological agents for creating biological weapons, their existing classification by degree of pathogenicity, method of penetration, etc., to identify the main properties of these microorganisms in the forensic aspect, systematize them to determine the tactics of the investigation at the initial stage of the investigation.Scientific works of microbiologists, virologists, biologists, epidemiologists and military epidemiologists devoted to the biological agents and the weapon, the methods of indication of bacteriological materials, also the works of criminologists devoted to the theory and practice of investigating special types of crime served as a basis to this article.Key words: act of terrorism, pathogenic microorganism, biological agents, especially dangerous infections, biological weapon, virus, pathogenic bacterial, rickettsia, toxins, tactics, investigative actions.